(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Coastal marine ecosystems, including coral reefs, mangroves, and seagrass meadows, are increasingly threatened by climate change, which disrupts ecological balances and jeopardizes biodiversity. Rising sea temperatures, ocean acidification, and altered salinity levels significantly affect marine species' survival, reproduction, and distribution. Additionally, extreme weather events and sea-level rise exacerbate habitat loss, with cascading effects on species reliant on these ecosystems. This paper explores the multifaceted impacts of climate change on coastal marine biodiversity, emphasizing the interconnectedness between environmental stressors and ecosystem resilience. Key drivers such as thermal stress, acidification, and eutrophication are examined in the context of their combined effects on primary productivity, trophic dynamics, and ecosystem services. The study also highlights adaptive responses observed in marine organisms, such as range shifts and phenological changes, while discussing their limitations in countering rapid environmental shifts. Furthermore, it investigates human contributions to climate stressors and the socio-economic consequences of biodiversity loss on fisheries, tourism, and coastal protection. Mitigation strategies, including marine protected areas, habitat restoration, and carbon sequestration initiatives, are reviewed as essential tools to bolster ecosystem resilience. This work underscores the urgent need for integrated, multidisciplinary approaches to combat climate change and safeguard coastal marine ecosystems, ensuring their continued provision of critical ecological and socio-economic benefits for future generations.